Current Vol. 8 No. 1 - Peggy Hinz:::Editor::: (Office of University Advancement, California State University Channel Islands)
GROWING A CAMPUS Building a university does not begin with the laying of bricks and mortar. Rather, the growth of a campus begins with the development of an academic core for students. All ensuing steps emanate from that foundation. At CSUCI, every decision about our physical campus planning and construction is based on the best interests of the students of today and those who will follow. This edition of Current features our progress to date in this area. As I have expressed to our campus family and the community at large, we must stay ever committed to providing the highest quality education possible for our students. This means developing a campus that evolves along with the needs of our student body, as well as the faculty and staff who are here to support them. For a time, our student enrollment will hold steady, in response to the current state budget situation. Nonetheless, I have an enrollment management team working to ensure that we accept every single student we can within the parameters that we have been given. Yet, students must have access to quality programs or there is no true access. At CSUCI, we are committed to that quality. To that end, we are staying on course with our planning and also using this time to evaluate our progress and programs. In addition, we are currently developing a five-year academic plan. We will not let our planning be scaled back by current circumstances. Through prudent planning of both our physical and academic goals, we won't have to wait to see what the future may hold; we are helping to define it. We are fortunate to have other sources of funding for projects such as student housing, the continuation of the University Glen residential development, and the Town Center. Each of these projects also represents critical developments that will generate income and help to ensure that we remain an outstanding jewel in the crown of the CSU system.